Indium Oxide Nanospirals Made of Kinked Nanowires - Shen, Guozhen; Liang, Bo; Wang, Xianfu; Chen, Po-Chiang; Zhou, Chongwu (ACS nano, 2011)
Helical inorganic nanostructures have received great attention due to their unique structures that could be interesting for both fundamental research and nanodevice applications. Using a tube-in-tube laser ablation chemical vapor deposition (CVD) method with gold nanoparticles as the catalysts, we reported the synthesis of self-assembled kinked In2O3 nanospirals and multikinked nanowires. As-synthesized nanostructures showed ultrafast photoinduced reversible wettability switching behavior from hydrophobic (132.7°) to superhydrophilic (0°) within 14 min. Single kinked In2O3 nanostructure-based field-effect transistors were fabricated, and mobilities higher than 200 cm2/(V·s) were obtained, revealing good opportunity in fabricating high-performance electronic and optoelectronic devices.